PENGELOLAAN STRES PADA SISWA SEKOLAH MENENGAH DI JAKARTA - Hastuti, Rahmah; Budiarto, Yohanes (Jurnal Bakti Masyarakat Indonesia, 2019)
Community service activities is intended to apply relaxation techniques to reduce stress on students in the middle school. The event was held at the students of SMP Muhammadiyah 33, Tomang, West Jakarta. This event is based on a complaint from the principal that values need to be briefed for the students in the school associated with the need to reduce the stress students in learning. Strategies to reduce stress provided through implementation of relaxation techniques, so that the students were able to perform stress coping presented in an interactive, exposure to the material of speakers also use educational games and video content. PKM activity was held on March 2, 2017 and engage learners and teachers. Based on the analysis, it is concluded that relaxation techniques are effective in lowering the stress levels of students. Mechanical belly breathing (abdominal breathing), deep muscle relaxation and meditation (simple meditation) was able to make students become more relaxed and calm so that the stress level is low. ABSTRAK: Kegiatan pelayanan masyarakat dimaksudkan untuk menerapkan teknik relaksasi untuk mengurangi stres pada siswa di sekolah menengah. Acara yang digelar di sekolah SMP Muhammadiyah 33, Tomang, Jakarta Barat. Peristiwa ini didasarkan pada keluhan dari kepala sekolah bahwa nilai-nilanya perlu diberi pengarahan untuk siswa di sekolahnya yang terkait dengan kebutuhan untuk mengurangi stress siswa dalam belajar. Strategi untuk mengurangi stres yang diberikan melalui pelaksanaan teknik relaksasi, sehingga siswa mampu melakukan Stres mengatasi disajikan dalam interaktif, paparan materi pembicara juga menggunakan permainan pendidikan dan konten video. PKM kegiatan yang diselenggarakan pada tanggal 2 Maret 2017 dan melibatkan peserta didik dan guru. Berdasarkan analisis, disimpulkan bahwa teknik relaksasi efektif dalam menurunkan tingkat stres siswa. Pernapasan perut mekanik (pernapasan perut), relaksasi otot dalam dan meditasi (meditasi sederhana) mampu membuat siswa menjadi lebih santai dan tenang sehingga tingkat stres rendah